Software testing - Sundaram, R. M. D. (Narosa, 2019)
Software Testing is a textbook which serves as a ready-reckoner for software developers and practitioners. Software testing needs to provide an unbiased and independent view to allow entrepreneurs to understand the risks of software implementation. As an elective or complement to courses on software engineering and software project management, software testing plays an important role. The book is helpful for undergraduate and post graduatestudents majoring in computer science, computer applications, information technology or information science.